Open surgical retrieval of a migrated patent foramen ovale closure device from the descending aorta following failed percutaneous retrieval from the aortic arch: a case report with a word of caution. Issue 3 (28th February 2023) - Berk, Thirza A; Kroeze, Sven; Suttorp, Maarten Jan; Heijmen, Robin H
Abstract: Background: Percutaneous patent foramen ovale (PFO) closure is considered safe and has been used widely for over 25 years. A rare but potentially life-threatening complication is device migration, especially to the aorta. Case summary: We present a 30-year-old male with a PFO occlusion device implanted for cryptogenic stroke, which asymptomatically migrated to the aortic arch. A percutaneous retrieval attempt failed at complete removal but relocated the device to the proximal descending aorta. It was then successfully removed by open surgery. Severe intimal damage necessitated resection and interposition grafting. Discussion: Manipulation of migrated intravascular devices can cause intimal damage and subsequent complications, such as local dissections. We advocate caution with percutaneous removal of such large, migrated closure devices to avoid additional intimal damage, especially after endothelialization has occurred. The interventional cardiologist should be aware of the risk of intimal damage as a result, and surgical removal, though invasive, should always be considered.